Lanthanum doped organic / inorganic nano-grid hybrid luminescent material and preparation method thereof
Through the hybrid luminescent material doped with lanthanum-doped organic/inorganic nanogrid, the combination of induced crystallization and efficient luminescent properties solves the problem that it is difficult to achieve both properties in the same material at the same time in the prior art, and improves the polyester Crystallization rate and mechanical properties, and impart their fluorescence properties.
Patent Information
- Application Number
- CN202310433394.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-04-21
AI Technical Summary
The prior art is difficult to achieve induced crystallization and efficient luminescence in the same polymer material at the same time, and there is a lack of additives that can combine these two properties.
The preparation method of hybrid luminescent materials using lanthanum doped organic/inorganic nanogrids is used to form nanostructures through the synthesis of silicon-diolide and lanthanide ion complexes, and combine them with linear polyester to achieve induced crystallization. and efficient glow.
The thermal crystallization temperature, relative crystallinity and mechanical properties of linear polyester are improved, while imparting the fluorescent properties of polyester, broadening the application fields of polyester materials.
Smart Images

Figure CN116463116B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of PET modification, in particular to a lanthanum-doped organic / inorganic nano-grid hybrid luminescent material and a preparation method thereof. Background Art
[0002] At present, PET has become the fastest growing variety in the non-fiber field after polyester for film and bottle. It is widely used in industry, agriculture, national defense and people's daily life. In recent years, people have paid great attention to polyester and polyester modification. In recent years, people have paid great attention to polyester and polyester modification. PET molecules have high structural regularity and strong crystallization ability, but due to the high rigidity of its molecular chain and high glass transition temperature, the movement of its molecular chain is hindered, so PET is only a semi-crystalline substance. In view of the disadvantage of PET's slow crystallization speed, people continue to study PET modification and continuously develop a variety of nucleating agents that make PET crystallize quickly, including inorganic nucleating agents, organic nucleating agents, and polymer nucleating agents, each of which has its own advantages and disadvantages. At present, it is rare to report that the same material has both induced crystallization and high-efficiency luminescence additives in the same polymer material at home and abroad, so it is of great significance to seek a preparation method of a hybrid luminescent material that can combine induced crystallization and high-efficiency luminescence. Summary of the invention
[0003] The object of the present invention is to provide a hybrid luminescent material of lanthanum doped organic / inorganic nano-grid and a preparation method thereof, so as to obtain a nucleation-inducing additive with high-efficiency luminescence.
[0004] The technical solution of the present invention is as follows:
[0005] A method for preparing a lanthanum-doped organic / inorganic nano-grid hybrid luminescent material comprises the following steps:
[0006] Silicon-diol compounds in organic / inorganic nano-grids: Silicon-diol compounds are obtained by reacting diol small molecules / polymers with tetrasilicate silicon sources at different molar ratios in a dry inert atmosphere without solvent or catalyst.
[0007] Synthesis of lanthanide ion complexes: Ln 3+ Ion and 1-2 conjugated small molecules: β-diketone and / or base, configured as Ln 3 + Rare earth complexes;
[0008] Synthesis of the nanostructure of lanthanum-doped organic / inorganic nanogrid: after dimethyl terephthalate and ethylene glycol react at a certain temperature for 1-4 hours under the action of catalyst zinc acetate, add condensation catalyst antimony trioxide and heat stabilizer triphenyl phosphite, react for half an hour, increase the temperature and continue to react for 1-3 hours, then add the silicon-diol compound, continue to react for 1-3 hours to obtain the organic / inorganic nanogrid; dissolve the synthesized organic / inorganic nanogrid in phenol and tetrachloroethane, mix it with the lanthanide ion complex, react for several hours at a certain temperature, wash it with acetone and ethanol, and vacuum dry it to obtain the hybrid luminescent material of lanthanum-doped organic / inorganic nanogrid.
[0009] The preparation method, the Ln 3+ Ions that emit light in the visible region of the spectrum when exposed to ultraviolet radiation, including Eu which emits red light 3+ , Tb emits green light 3+ , Sm emits orange light 3+ , emitting blue light Tm 3+ .
[0010] In the preparation method, the β-diketone includes acetylacetone ACAC, benzoyl acetone BA, dibenzoylmethane DBM, trifluoroacetylacetone TFA or thienyl methane trifluoroacetone TTA.
[0011] In the preparation method, the base comprises o-phenanthroline Phen, piperidine Pip or NaOH.
[0012] In the preparation method, the tetrasilicate silicon source includes tetraethyl orthosilicate TEOS, tetrapropyl orthosilicate TPOS or tetrabutyl orthosilicate TBOS.
[0013] The preparation method, the diols are generally formulated as C n H (2n+2) O m .
[0014] The preparation method comprises the following specific steps:
[0015] Synthesis of silicon-diol compound: 0.32mol of diol small molecules / polymers were added to a three-necked round-bottom flask purged with nitrogen flow. The three-necked flask was connected to a reflux condenser, a constant pressure separatory funnel and a nitrogen gas device. After magnetic stirring for 0.5h, 0.08mol of freshly distilled tetrasilicic acid ester silicon source was added dropwise through a separatory funnel. The first drop of by-product collected was considered to be the beginning of the reaction. The reaction temperature was 140°C and remained stable until the end of the reaction (15h). The crude reaction product was concentrated under vacuum to obtain a viscous liquid.
[0016] Lanthanum-doped organic / inorganic nanomesh nanostructures3+ Rare earth complex: weigh a certain amount of lanthanide salt to prepare a 0.1 mol / L lanthanide salt solution, weigh a certain amount of β-diketone to prepare a 0.1 mol / L β-diketone solution, and then weigh a certain amount of alkali to prepare a 0.1 mol / L alkali solution; weigh the lanthanide salt solution and β-diketone solution of the prepared concentrations respectively, stir magnetically for 1 hour, then add the alkali solution, the volume ratio of the three solutions is 1:3:1, adjust the pH value to 6-7 with 1 mol / L dilute ammonia water, stir for 2.5 hours, and prepare Ln 3+ Organic ligand complex. Hybrid luminescent material of lanthanum doped organic / inorganic nano-grid: 31.069g dimethyl terephthalate (DMT), 20.522mL ethylene glycol (EG), and a small amount of zinc acetate were added to a 150mL three-necked flask, reacted at 190℃ for 2h, and methanol was produced as a byproduct; then a small amount of polycondensation catalyst Sb2O3 and 2-3 drops of triphenyl phosphite (TPP) were added, and the reaction was continued for 0.5h; the temperature was raised to 230℃, and the reaction was continued for 2h; then the obtained silicon-diol compound was added and reacted for 3h, and the obtained product was quickly poured into 300mL distilled water, cooled, filtered, and freeze-dried to obtain a solid powder containing an organic / inorganic nano-network structure. The synthesized organic / inorganic nano-grid was dissolved in phenol and tetrachloroethane, and then stirred with the Ln3+ organic ligand complex at room temperature for 30 minutes. The molar ratio of the lanthanide organic ligand complex to the organic / inorganic nano-grid was 1:1, and the reaction was continued at 70℃ for 6h. The product was washed with acetone and ethanol and dried in vacuo to obtain a hybrid luminescent material of lanthanum-doped organic / inorganic nano-grid.
[0017] The preparation method comprises the following specific steps:
[0018] Silicon-polyethylene glycol compounds in organic / inorganic nanogrids: 0.32 mol of polyethylene glycol (Mn=200) was added to a three-necked round-bottom flask purged with nitrogen flow, and the three-necked flask was respectively connected to a reflux condenser, a constant pressure separatory funnel and a nitrogen gas device. After magnetic stirring for 0.5 h, 0.08 mol of freshly distilled tetraethyl orthosilicate TEOS 8.960 mL was added dropwise through a separatory funnel. The first drop of ethanol collected was considered to be the start of the reaction; the reaction temperature was 140°C and kept stable until the end of the reaction; the crude reaction product was concentrated under vacuum to obtain a viscous liquid;
[0019] Eu in the nanostructure of europium-doped organic / inorganic nanomesh 3+Rare earth complex: Weigh a certain amount of europium chloride to make a 0.1mol / L EuCl3 solution, weigh a certain amount of TTA to make a 0.1mol / L TTA solution, and then weigh a certain amount of o-phenanthroline to make a 0.1mol / L Phen solution; weigh the prepared EuCl3 solution and TTA solution respectively, stir magnetically for 1h, then add Phen solution, the volume ratio of the three solutions is 1:3:1, adjust the pH value to 6-7 with 1mol / L dilute ammonia water, stir for 2.5h, and prepare EuCl3 solution. 3+ Organic ligand complexes;
[0020] Europium-doped organic / inorganic nano-grid hybrid luminescent material: 31.069g dimethyl terephthalate (DMT), 20.522mL ethylene glycol (EG), and a small amount of zinc acetate were added to a 150mL three-necked flask, and reacted at 190°C for 2h to produce methanol as a byproduct; then a small amount of polycondensation catalyst Sb2O3 and 2-3 drops of triphenyl phosphite (TPP) were added, and the reaction lasted for 0.5h; the temperature was raised to 230°C and the reaction lasted for 2h; then the obtained silicon-polyethylene glycol compound was added and reacted for 3h, and the obtained product was quickly poured into 300mL distilled water, cooled, filtered, and freeze-dried to obtain a solid powder containing an organic / inorganic nano-grid structure. The synthesized organic / inorganic nano-grid was dissolved in phenol and tetrachloroethane, and then mixed with Eu 3+ The organic ligand complex was stirred at room temperature for 30 minutes. 3+ The molar ratio of the organic ligand complex to the organic / inorganic nano-grid is 1:1, and the mixture is reacted at 70° C. for 6 hours, washed with acetone and ethanol, and dried in vacuum to obtain a hybrid luminescent material of the organic / inorganic nano-grid doped with europium.
[0021] The lanthanum-doped organic / inorganic nano-mesh hybrid luminescent material is prepared according to any method.
[0022] The lanthanum-doped organic / inorganic nano-grid hybrid luminescent material is added to linear polyester at a ratio of 0.25-4wt% to improve the thermal crystallization temperature, relative crystallinity and mechanical properties of the linear polyester.
[0023] The application is to add the polyester to the linear polyester at a ratio of 0.25-0.75 wt% or to add the polyester to the linear polyester at a ratio of 0.75 wt%.
[0024] The present invention has the following beneficial effects:
[0025] 1. The present invention constructs a new nano-nucleation-induced and highly efficient luminescent grid material with inorganic silicon atom expansion, block polymer regulation, and lanthanum ion complex embedding through an overall design of the hybrid luminescent material.
[0026] 2. The obtained hybrid luminescent material of lanthanum doped organic / inorganic nano-grid uses silicon atom as the starting atom, and the tetrasilicic acid tetraester silicon source and diol polymer undergo tetrafunctional esterification reaction, and low molecular weight polyethylene terephthalate with similar or identical structure to the matrix polymer is externally connected to form a silicon-linked molecular network, and at the same time, the lanthanum ion complex is anchored in the grid to form an organic / inorganic nano-grid structure loaded with lanthanide complexes. The lanthanum ion complex gives polyester fluorescent properties, which broadens the application field of PET-based composite materials;
[0027] 3. For the polymer matrix, the short polymer matrix chain segments (LMPET) grafted on the surface of the silicon nanomesh toward its outer edge induce crystallization of the polymer matrix due to crystallization nucleation. In addition, the lanthanum ions form a tight coordination with the carbonyl (O=C) in the ester group of LMPET. Different carbonyl groups on the same LMPET chain segment can react with different lanthanum ions, and a single lanthanum ion can also attach to different LMPET chains. This diverse coordination reaction causes the lanthanum ions to form crosslinks in the inorganic / organic nanomesh, making the inorganic / organic nanomesh more tightly entangled, thereby increasing the crystallization rate of the polymer matrix; especially diol polymers, which are flexible short block segments, realize the grafting of flexible segments on the rigid skeleton molecular structure of PET, which neither changes the original properties of PET nor effectively improves the limitations caused by its rigid structure, thereby enhancing the mechanical properties of polyester. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the process of the present invention;
[0029] Figure 2 The DSC cooling and heating curves of hybrid luminescent materials with different addition amounts of PET-based europium doped organic / inorganic nano-grids;
[0030] Figure 3 The DSC cooling and heating curves of the hybrid materials of PET-based organic / inorganic nano-mesh with different addition amounts;
[0031] Figure 4 A comparison diagram of the relative crystallinity of PET-based europium-doped organic / inorganic nanomesh hybrid materials with different addition amounts and PET-based organic / inorganic nanomesh hybrid materials;
[0032] Figure 5 These are the fluorescence excitation and emission spectra of different amounts of nucleating agent added to industrial polyester. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with specific embodiments.
[0034] Example 1
[0035] The present invention discloses a method for preparing a hybrid luminescent material of lanthanum-doped organic / inorganic nano-grid and its application, comprising the following steps:
[0036] Silicon-diol compounds in organic / inorganic nanogrids: In a dry inert atmosphere and without solvent or catalyst, diol small molecules / polymers are reacted with tetrasilicate silicon sources at different molar ratios to obtain silicon-diol compounds, effectively dealcoholizing and condensing the hydroxyl groups at the ends of the diols with the ester groups of the tetrasilicate silicon sources.
[0037] Formation of lanthanide ion complexes in lanthanum-doped organic / inorganic nanomesh: Ln 3+ Ions and 1-2 conjugated small molecules: β-diketone, base, are configured into Ln in a certain proportion under certain conditions. 3+ Rare earth complexes, while grafting short block copolymers on the surface of organic / inorganic networks, 3+ The complex solution is added into the reaction system to obtain lanthanum-doped organic / inorganic nano-grids.
[0038] Synthesis of the nanostructure of lanthanum-doped organic / inorganic nanogrid: dimethyl terephthalate and ethylene glycol react at 190°C for 1-4 hours under the action of zinc acetate catalyst, then add polycondensation catalyst antimony trioxide and heat stabilizer triphenyl phosphite, react for half an hour, heat to 230°C and react for another 1-3 hours, then add the silicon-diol compound obtained above, continue to react for 1-3 hours, and obtain the nanostructure of organic / inorganic nanogrid. The synthesized organic / inorganic nanogrid is dissolved in phenol and tetrachloroethane (mass ratio 1:1), then mixed with lanthanide ion complex, react at 70°C for 3-6 hours, washed with acetone and ethanol, and dried in vacuum to obtain the hybrid luminescent material of lanthanum-doped organic / inorganic nanogrid.
[0039] The preparation method of the hybrid luminescent material of lanthanum doped organic / inorganic nano-grid, the Ln 3+ Ions that emit light in the visible region of the spectrum when exposed to ultraviolet radiation, including Eu which emits red light 3+ , Tb emits green light 3+ , Sm emits orange light 3+ , emitting blue light Tm 3+ .
[0040] The preparation method of the hybrid luminescent material of lanthanum doped organic / inorganic nano-grid, the β-diketone includes acetylacetone ACAC, benzoyl acetone BA, dibenzoylmethane DBM, trifluoroacetylacetone TFA and thienyl methane trifluoroacetone TTA, which are commercially available in analytical grade.
[0041] The method for preparing a lanthanum-doped organic / inorganic nano-grid hybrid luminescent material, the base comprises o-phenanthroline Phen, piperidine Pip, and NaOH, which are commercially available in analytical grade.
[0042] The preparation method of the hybrid luminescent material of lanthanum doped organic / inorganic nano-grid, the tetrasilicate silicon source includes tetraethyl orthosilicate TEOS, tetrapropyl orthosilicate TPOS, and tetrabutyl orthosilicate TBOS, which are commercially available in analytical grade.
[0043] The preparation method of the hybrid luminescent material of lanthanum doped organic / inorganic nano-grid, wherein the general formula of the polyol is C n H (2n+2) O m , commercially available analytical grade.
[0044] Among them, low molecular weight PET is polyethylene terephthalate, which is a crystalline saturated polyester with a molecular weight ranging from several thousand to ten thousand.
[0045] Example 2
[0046] The present invention discloses a method for preparing a hybrid luminescent material of lanthanum-doped organic / inorganic nano-grid and its application, comprising the following steps:
[0047] Synthesis of silicon-polyethylene glycol compound: 0.32 mol of polyethylene glycol (Mn=200) was added to a three-necked round-bottom flask purged with nitrogen flow, and the three-necked flask was connected to a reflux condenser, a constant pressure separatory funnel and a nitrogen gas device respectively. After magnetic stirring for 0.5 h, 0.08 mol of freshly distilled tetraethyl orthosilicate TEOS (8.960 mL) was added dropwise through a separatory funnel. The reaction temperature was 140°C and kept stable until the reaction was completed (15 h). The crude reaction product was concentrated under vacuum to obtain silicon-polyethylene glycol compound.
[0048] Eu 3+ Synthesis of organic ligand complex: 0.1 mol / L EuCl3 solution and 0.1 mol / L TTA solution were measured respectively, magnetically stirred for 1 h, and then 0.1 mol / L Phen solution was added, the volume ratio of the three solutions was 1:3:1, and the pH value was adjusted to 6-7 with 1 mol / L dilute ammonia water, stirred for 2.5 h, and Eu was prepared. 3+ Organic ligand complexes.
[0049] Synthesis of hybrid luminescent materials of europium-doped organic / inorganic nano-grids: 31.069g of dimethyl terephthalate (DMT), 20.522mL of ethylene glycol (EG), and a small amount of zinc acetate were added to a 150mL three-necked flask, and reacted at 190°C for 2h to produce methanol as a byproduct; then a small amount of polycondensation catalyst Sb2O3 and 2-3 drops of triphenyl phosphite (TPP) were added, and the reaction lasted for 0.5h; the temperature was raised to 230°C and the reaction lasted for 2h; then the obtained silicon-polyethylene glycol compound was added and reacted for 3h, and the obtained product was quickly poured into 300mL of distilled water for cooling, filtration, and freeze-drying to obtain a solid powder containing an organic / inorganic nano-network structure. The synthesized organic / inorganic nano-grid was dissolved in phenol and tetrachloroethane (mass ratio 1:1), and then mixed with Eu 3+ The organic ligand complex was stirred at room temperature for 30 minutes. 3+ The molar ratio of the organic ligand complex to the organic / inorganic nano-grid is 1:1), and the mixture is reacted at 70° C. for 6 hours, washed with acetone and ethanol, and dried in vacuum to obtain a hybrid luminescent material of the organic / inorganic nano-grid doped with europium.
[0050] Wherein, polyethylene glycol 200 and tetraethyl orthosilicate were commercially available of analytical grade.
[0051] Example 3
[0052] Experimental purpose and method: In order to study the effect of lanthanum-doped organic / inorganic nano-mesh hybrid luminescent material on the crystallization kinetics of linear polyester crystallization, this example uses the europium-doped organic / inorganic nano-mesh hybrid luminescent material synthesized in Example 2 as the experimental object, and the organic / inorganic nano-mesh synthesized in Example 2 as the control group object to study its effect on the crystallization kinetics and luminescent effect of linear polyester chips. The specific method is: the DSM Xplore 5&15 type micro-blender melt blending method is used to fully mix, and a standard sample is made in a DSM Xplore 10cc type micro-injection molding machine. The melting temperature in the blender was 290°C, and the mold temperature in the injection molding machine was 110°C. Eight groups of samples of synthesized PET-based europium-doped organic / inorganic nanomesh hybrid luminescent materials at 0%, 0.25%, 0.5%, 0.75%, 1%, 2%, 3%, and 4% were prepared for testing of mechanical properties (Table 3), crystallization properties (Table 1), and fluorescence properties. In addition, eight groups of samples of synthesized PET-based organic / inorganic nanomesh hybrid materials at 0%, 0.25%, 0.5%, 0.75%, 1%, 2%, 3%, and 4% were tested for crystallization properties (Table 2) and compared with the experimental objects.
[0053] Table 1: Crystallization data of modified luminescent polyesters doped with Eu complexes
[0054]
[0055] Table 2: Crystallization data of modified polyesters without Eu complex doping
[0056]
[0057] Table 3: Mechanical properties of modified luminescent polyesters doped with Eu complexes
[0058]
[0059]
[0060] As shown in Table 1-2 and Figure 2-4 As shown in the figure, under the same conditions, the thermal crystallization peak Tc value of the nanostructured PET-based composite material with the addition of organic / inorganic nanogrids is higher than that of pure PET, and the crystallization peak is stronger. When the addition amount is 0.75%, the cold crystallization peak temperature and intensity are the highest, indicating that the crystallization rate of the PET-based polyester is faster at this time. This is because when a small amount of organic / inorganic nanogrids are blended into the PET melt, the heterogeneous nucleation of the PET matrix is promoted, accelerating the nucleation and crystallization of PET. At the same time, the soft chain part makes the PET chain movement more active, improves the crystallization, and increases the crystallinity. When a small amount of PET-based europium-doped organic / inorganic nanogrid hybrid luminescent material is blended into the PET melt, the thermal crystallization temperature first increases and then decreases, and when the addition amount is 0.75%, the highest crystallization temperature and relative crystallinity appear, promoting the best effect of PET-based nucleation. Therefore, the nucleation-promoting effect of the additive is not weakened before and after doping with the lanthanide complex, but is enhanced. From Figure 5 It can be seen that a small amount of addition makes the industrial polyester have an excitation peak at a wavelength of 345nm and an emission peak at a wavelength of 617nm, which makes the polyester have luminescent properties. As can be seen from Table 3, after adding the nanostructure of europium doped organic / inorganic nanomesh, the mechanical properties of polyester are greatly improved, especially 0.75%, the tensile strength, modulus and elongation at break of the material are greatly improved. The reason for the above crystallization is that when the nanostructure of the europium-doped organic / inorganic nanogrid is blended in a small amount into the polyethylene terephthalate melt, the nanostructure of the europium-doped organic / inorganic nanogrid acts as a nucleation center, promotes the heterogeneous nucleation of the PET matrix, accelerates the nucleation and crystallization of the PET, and at the same time, the soft chain part makes the PET chain movement more active, improves the crystallization, and increases the crystallinity; and the shearing effect of the low-content additive blended with the industrial polyester in the twin-screw micro-blender makes the additive well dispersed in the PET polyester, so that the adsorption capacity between the polymer chains is enhanced, and accompanied by a certain degree of entanglement and cross-linking, a network structure is formed. Under the action of shear force, the strong adhesion between the two makes the mechanical properties of the PET matrix higher than those of pure PET.
[0061] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.
Claims
1. A method for preparing a hybrid luminescent material of lanthanum doped organic / inorganic nano-grid, characterized in that: The following steps are involved: Synthesis of silicon-diol compounds: 0.32 mol of diol small molecules / polymers were added to a three-necked round-bottom flask purged with nitrogen flow. The three-necked flask was connected to a reflux condenser, a constant pressure separatory funnel and a nitrogen gas device. After magnetic stirring for 0.5 h, 0.08 mol of freshly distilled tetrasilicate silicon source was added dropwise through a separatory funnel. The first drop of by-product collected was considered to be the beginning of the reaction. The reaction temperature was 140°C and kept stable until the reaction ended after 15 h. The crude reaction product was concentrated under vacuum to obtain a viscous liquid. Lanthanum-doped organic / inorganic nanomesh nanostructures 3+ Rare earth complex: weigh a certain amount of lanthanide salt to prepare a 0.1 mol / L lanthanide salt solution, weigh a certain amount of β-diketone to prepare a 0.1 mol / L β-diketone solution, and then weigh a certain amount of alkali to prepare a 0.1 mol / L alkali solution; weigh the lanthanide salt solution and β-diketone solution of the prepared concentrations respectively, stir magnetically for 1 hour, then add the alkali solution, the volume ratio of the three solutions is 1:3:1, adjust the pH value to 6-7 with 1 mol / L dilute ammonia water, stir for 2.5 hours, and prepare Ln 3+ Organic ligand complex; hybrid luminescent material of lanthanum-doped organic / inorganic nanogrid: 31.069g dimethyl terephthalate (DMT), 20.522mL ethylene glycol (EG), and a small amount of zinc acetate were added to a 150mL three-necked flask, and reacted at 190°C for 2h to produce methanol as a byproduct; then a small amount of polycondensation catalyst Sb2O3 and 2-3 drops of triphenyl phosphite (TPP) were added, and the reaction was continued for 0.5h; the temperature was raised to 230°C and the reaction was continued for 2h; then the obtained silicon-diol compound was added to react The reaction was carried out for 3 hours, and the obtained product was quickly poured into 300 mL of distilled water for cooling, filtering, and freeze-drying to obtain a solid powder containing an organic / inorganic nano-network structure; the synthesized organic / inorganic nano-grid was dissolved in phenol and tetrachloroethane, and then stirred with the Ln3+ organic ligand complex at room temperature for 30 minutes, the molar ratio of the lanthanide organic ligand complex to the organic / inorganic nano-grid was 1:1, and the reaction was carried out at 70°C for 6 hours; the product was washed with acetone and ethanol, and dried in vacuum to obtain a hybrid luminescent material of lanthanum-doped organic / inorganic nano-grid.
2. A method for preparing a hybrid luminescent material of lanthanum-doped organic / inorganic nano-grid, characterized in that: The following steps are involved: Silicon-polyethylene glycol compounds in organic / inorganic nanogrids: 0.32 mol polyethylene glycol (Mn=200) was added to a three-necked round-bottom flask purged with nitrogen flow. The three-necked flask was connected to a reflux condenser, a constant pressure separatory funnel and a nitrogen gas device. After magnetic stirring for 0.5 h, 0.08 mol of freshly distilled tetraethyl orthosilicate TEOS 8.960 mL was added dropwise through a separatory funnel. The first drop of ethanol collected was considered to be the start of the reaction. The reaction temperature was 140°C and kept stable until the end of the reaction. The crude reaction product was concentrated under vacuum to obtain a viscous liquid. Eu in the nanostructure of europium-doped organic / inorganic nanomesh 3+ Rare earth complex: Weigh a certain amount of europium chloride to make a 0.1mol / L EuCl3 solution, weigh a certain amount of TTA to make a 0.1mol / L TTA solution, and then weigh a certain amount of o-phenanthroline to make a 0.1mol / L Phen solution; weigh the prepared EuCl3 solution and TTA solution respectively, stir magnetically for 1h, then add Phen solution, the volume ratio of the three solutions is 1:3:1, adjust the pH value to 6-7 with 1mol / L dilute ammonia water, stir for 2.5h, and prepare EuCl3 solution. 3+ Organic ligand complexes; Europium-doped organic / inorganic nano-grid hybrid luminescent material: 31.069 g of dimethyl terephthalate (DMT), 20.522 mL of ethylene glycol (EG), and a small amount of zinc acetate were added to a 150 mL three-necked flask, and reacted at 190 ° C for 2 hours to produce methanol as a byproduct; then a small amount of polycondensation catalyst Sb2O3 and 2-3 drops of triphenyl phosphite (TPP) were added, and the reaction was continued for 0.5 hours; the temperature was raised to 230 ° C and the reaction was continued for 2 hours; then the obtained silicon-polyethylene glycol compound was added and reacted for 3 hours, and the obtained product was quickly poured into 300 mL of distilled water for cooling, filtering, and freeze-drying to obtain a solid powder containing an organic / inorganic nano-grid structure; the synthesized organic / inorganic nano-grid was dissolved in phenol and tetrachloroethane, and then mixed with Eu 3+ The organic ligand complex was stirred at room temperature for 30 minutes. 3+ The molar ratio of the organic ligand complex to the organic / inorganic nano-grid is 1:1, and the mixture is reacted at 70°C for 6 hours; the mixture is washed with acetone and ethanol, and dried in vacuum to obtain a hybrid luminescent material of the organic / inorganic nano-grid doped with europium.
3. A lanthanum-doped organic / inorganic nano-mesh hybrid luminescent material prepared according to the preparation method of claim 1 or 2.
4. The use of the hybrid luminescent material of lanthanum doped organic / inorganic nano-grid according to claim 3, characterized in that: It is added to linear polyester at a ratio of 0.25-4wt% to improve the thermal crystallization temperature, relative crystallinity and mechanical properties of linear polyester.
Citation Information
Patent Citations
Preparation method of PET-base europium complexed and hybridized light-emitting material
CN107325498A